The Training of the Child in Jacobu - Kwofie, B. (Institute of Education, Achimota., 1953)
The following pages contain the results of my research on Child Training in my own village, Jacobu. Jacobu is one of the subordinate villages in the Bekwai District, Ashanti. It is situated on a hill to the north-west of Bekwai, and it covers an area of about three- quarters of a square mile with a population of about two thousand inhabitants.
Keywords: Child Training; Culture; Jacobu